Nanoscale momentum-resolved vibrational spectroscopy - Hage, F; Nicholls, R; Yates, J; McCulloch, D; Lovejoy, T; Dellby, N; Krivanek, O; Refson, K; Ramasse, Q (American Association for the Advancement of Science, 2018)
Vibrational modes affect fundamental physical properties such as the conduction of sound and heat and can be sensitive to nano- and atomic-scale structure. Probing the momentum transfer dependence of vibrational modes provides a wealth of information about a materials system; however, experimental work has been limited to essentially bulk and averaged surface approaches or to small wave vectors. We demonstrate a combined experimental and theoretical methodology for nanoscale mapping of optical and acoustic phonons across the first Brillouin zone, in the electron microscope, probing a volume ~10^10 to 10^20 times smaller than that of comparable bulk and surface techniques. In combination with more conventional electron microscopy techniques, the presented methodology should allow for direct correlation of nanoscale vibrational mode dispersions with atomic-scale structure and chemistry.